Physiological differences of elite and professional road cyclists related to competition level and rider specialization - Sallet, P.; Mathieu, R.; Fenech, G.; Baverel, G. (The Journal of Sports Medicine and Physical Fitness, 2006)
Aim: The aim of this investigation was to study the physiological response to laboratory tests in elite and professional cyclists, and to relate it to the level at which riders compete and their specialization. Methods: A total of 71 cyclists were divided into two groups, elite and professional, and were assessed for physical measurements, a maximal graded test and a 30 s all-out test, both performed on a cycle ergometer. The sample included 24 uphill riders (UR), 32 flat terrain riders (FTR), 11 all terrain riders (ATR) and 4 sprinters (SP). Results: Professional riders showed significantly higher gross mechanical efficiency (GME) that their elite counterparts (25.6±2.6 vs 24.4±2%), but otherwise no other physiological differences emerged from the comparison between these two groups. However, many differences exist as a function of rider specialization, especially between UR and FTR. Compared with FTR, UR showed a higher V.O2max (78.2±5.5 vs 72.6±6.5 mL.min-1.kg-1) and a lower maximal aerobic power (438.5±40.8 vs 465.3±36.2 W). From the 30 s all-out test, SP presents the highest maximal power (P<0.05) and maximal velocity (P<0.05) compared with all the other groups. Conclusions: The results for GME indicate a better efficiency for professional riders and suggest the importance of technical aspects related to movement pattern in cycling. The sensitivity of the maximal graded test and the 30 s all-out test did not allowed other differentiations between elite and professional cyclists.